Comparison of outcome following knee immobilization versus no immobilization in the immediate post operative period following arthroscopic anterior cruciate ligament reconstruction - Kumar, Debangshu; Kundu, Bishal (International Surgery Journal, 2022)
Background: Post operative bracing following ACL reconstruction has been traditionally used in post operative period to reduce pain limit knee range of motion to protect against valgus and varus stress. There is a lack of consensus in published literature regarding knee immobilization. The aim of this study is to compare the functional outcome and pain control in patients using knee immobilizer with those not using them in immediate post operative period. Methods: A total of 60 patients admitted with ACL tear who were admitted from January 2020 to August 2021 were enrolled in this study and randomised into two groups, given knee immobilizer or no immobilizer following arthroscopic ACL reconstruction. Patients were assessed for pain, knee range of motion and functional outcome with 6-month follow-up. Results: VAS score for pain was significantly lower for knee brace users (p=0.24) on post-op day2 but there was no significant difference on subsequent measurements. Also, the IKDC Score, arc of motion of knee joint and complication rate did not show significant difference between the two groups. Conclusions: Based on this study, the use of a knee brace for improving short term outcome following ACL reconstruction is not justified and adds to the cost of treatment. A short cylindrical back slab for 2-3days can serve the same purpose of controlling pain and soft tissue protection.